Politics of Water Resources Under the Impacts of Climate Change: Turkey and Beyond - Kibaroğlu, Ayşegül (The Faculty of Economics, Administrative and Social Sciences, Bilkent University and the Istanbul Policy Center, Sabancı University, 2015)
Climate change is frequently made out to be amongst the key security challenges of the 21st century. Not only popular media but also official policy documents and academic accounts frequently raise the alarm over the conflict potential in a future shaped by increasing variability and exacerbating change in climatic patterns. Nature that sustains us, as the socio-ecological metabolism of our modern societies, has now increasingly come to be seen as a threat to humanity’s very survival. The increase in mean temperatures, climate variability, extreme weather events and rising sea levels are but few of the many future scenarios anticipated to increase social vulnerability and trigger social unrest. Not only already volatile parts of Sub-Saharan Africa and Sahel but also the Mediterranean and the Middle East are said to be amongst the regions most exposed to climate risks, whereby geopolitical, social and climate instability coincide.
Keywords: Climate Change; Water Resources; Water Politics